Evidence-based quality leadership in orthopaedics. (2nd March 2022) - Silva, Geeth; Ashford, Robert U; Wildin, Clare J; Achan, Pramod
Abstract : There is a paucity of literature analysing the importance of leadership within trauma and orthopaedics. However, such skills are essential to make an orthopaedic surgeon proficient in their various roles. This literature review on leadership within orthopaedics enables an understanding of current issues. A narrative literature review was conducted using Pubmed, Medline and The National Centre for Biotechnology databases. The search string used to conduct the narrative literature review was (orthopaedic) and (leadership[Title]). The articles were screened by title, abstract and full text. A reference search was subsequently conducted on these papers using the same inclusion and exclusion criteria. The papers then underwent a thematic analysis to understand the issues surrounding leadership in orthopaedics. The critical themes recognised were quality improvement, training, women in leadership, inequality and traits of a leader. Through reviewing the themes in this article, a framework was developed to identify the current issues and potential avenues of advancing orthopaedic leadership. This narrative literature review has demonstrated a paucity of research in orthopaedic leadership. Further work would create a robust evidence base, outline ideal orthopaedic leadership and standardise training to create better orthopaedic leaders.